Dark minute nodules in andesite from the Fintice quarries (Eastern Slovakia), its character and possible origin - Košuth, Marian; Pawlikowski, Maciej; Bożęcki, Piotr (My University, 2014)
Crystals of pyroxene, plagioclase and ilmenite, present at andesite from Fintice, Eastern Slovakia – were examined using the traditional chemical analysis, polarizing light microscopy, scanning electron microscopy with EDS detect or and Raman spectroscopy. Special attention was paid to geochemical determination of rock forming phases crystal growth and to stages of its crystallization. Obtained data were used for reconstruction of these phases crystallization i.e. phases of alternation because of magma chemistry.
Drobne ciemne koncentracje w andezytach z kamieniołomu w Finticach (Wschodnia Słowacja), ich charakter i prawdopodobne pochodzenie
Auxiliary Sciences in Archaeology, Preservation of Relics and Environmental Engineering
No 11.11.140.319.
Keywords: spotty andesite; andezyty; extrusive bodies; Słowacja; dark enclaves; ciemne koncentracje